A nova era da virtualização do trabalho no judiciário: uma análise sobre o teletrabalho na Justiça Trabalhista no Maranhão - LIMA , Adriana Sousa (2021)
This research addresses telework in the Judiciary (main thematic axis) developed by servers (research subjects) of the Regional Labor Court of the 16th Region – TRT-16 (institution of justice), with an investigative focus on legal and health repercussions. In this context, this study aims to analyze the legal and health repercussions arising from teleworking on public servants working in the Labor Courts in Maranhão (TRT-16) based on the constitutional guarantee of the right to health (art. 196 of CF/88) and the Policy of Comprehensive Health Care for Magistrates and Servants of the Judiciary Power (Resolution CNJ n. 207/2015). From a methodological point of view, the research has a quali-quantitative approach and uses, predominantly, the inductive method and bibliographic and documentary research techniques, with emphasis on the documents of the National Council of Justice. It is also a field research with application of the case study method, considering the detailed examination of the telework category in a specific institutional environment (TRT-16), through the study of a certain target audience: teleservers working in this Labor Region. The research hypothesis – greater illness among TRT-16 teleworkers – was partially confirmed, only in 2018, by collating the absenteeism-illness index of servers (general) and teleservers.